1997
DOI: 10.1111/j.1365-2788.1997.tb00671.x
|View full text |Cite
|
Sign up to set email alerts
|

Behaviour problems associated with lack of speech in people with learning disabilities

Abstract: It has been observed in a population of people with learning disabilities that people with good understanding but no speech have significantly more behaviour problems than those with good speech. This observation was confirmed by testing a data set of 3662 people. The purpose of the study was to stress the importance of teaching communication techniques as early as possible in order to pre-empt behaviour problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 6 publications
0
29
0
Order By: Relevance
“…Whilst the literature regarding communication and self-injury generally suggests that more severe deficits in communication are associated with a higher prevalence of behavior, data regarding aggressive and destructive behaviors paint a rather more complicated picture. Some studies (Bott et al 1997) have reported increased rates of behavior associated with lower levels of expressive communication, whilst others have reported that a less severe deficit in communication is associated with a higher prevalence of challenging behavior (Emerson et al 2001). Rojahn et al (2004) calculated risk ratios for psychiatric conditions given various challenging behaviors and found that aggressive and destructive behavior represented a risk factor for the presence of language disorders.…”
Section: Discussionmentioning
confidence: 96%
“…Whilst the literature regarding communication and self-injury generally suggests that more severe deficits in communication are associated with a higher prevalence of behavior, data regarding aggressive and destructive behaviors paint a rather more complicated picture. Some studies (Bott et al 1997) have reported increased rates of behavior associated with lower levels of expressive communication, whilst others have reported that a less severe deficit in communication is associated with a higher prevalence of challenging behavior (Emerson et al 2001). Rojahn et al (2004) calculated risk ratios for psychiatric conditions given various challenging behaviors and found that aggressive and destructive behavior represented a risk factor for the presence of language disorders.…”
Section: Discussionmentioning
confidence: 96%
“…Consequently, language comprehension in low-functioning children with ASD is often overestimated, when they are approached at the level of their expressive language (Hudry et al 2010). Several previous studies demonstrated a significant relation between communication difficulties and the severity of challenging behavior in low-functioning individuals (Bott et al 1997;Chamberlain et al 1993;McClintock et al 2003). The study of Sigafoos (2000) showed that more severe deficits in receptive language compared to expressive language are associated with challenging behavior.…”
Section: Discussionmentioning
confidence: 98%
“…Challenging behavior has been associated with communication difficulties within both experimental (e.g. Bott, Farmer, & Rhode, 1997;Quine, 1986) and carer or support staff based questionnaire studies (e.g. Hastings, 1997).…”
Section: Behavioral Expression Of Emotionsmentioning
confidence: 99%